2021
DOI: 10.26434/chemrxiv.14236886.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Order from Disorder with Intrinsically Disordered Peptide Amphiphiles

Abstract: Amphiphilic molecules and their self-assembled structures have long been the target of extensive research due to their potential applications in fields ranging from materials design to biomedical and cosmetic applications. Increasing demands for functional complexity have been met with challenges in biochemical engineering, driving researchers to innovate in the design of new amphiphiles. An emerging class of molecules, namely, peptide amphiphiles, combines key advantages and circumvents some of the disadvanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 4 publications
2
18
0
Order By: Relevance
“…To show reversibility, we used a pH-responsive system of intrinsically disordered peptide amphiphiles (IDPAs (Jacoby et al ., 2021)). Specific amino acids in the used sequence can get protonated and become uncharged with decreasing pH.…”
Section: Chamber Designmentioning
confidence: 99%
“…To show reversibility, we used a pH-responsive system of intrinsically disordered peptide amphiphiles (IDPAs (Jacoby et al ., 2021)). Specific amino acids in the used sequence can get protonated and become uncharged with decreasing pH.…”
Section: Chamber Designmentioning
confidence: 99%
“…trinsically disordered carboxy tail-domain of neurofilament-light (NF-L) protein found in the cytoskeleton of nerve cells. [35][36][37]54 In previous research, 47 we introduced this IDP sequence to create IDPAs where aromatic branchings units were used to cap the N-terminus of the IDP sequence and allow the branching into two different types of architectures containing either two or four hydrocarbon tails (2×12, 4×7). We showed that these IDPAs undergo a sharp phase transition from low-dispersity micellar spheres to extremely elongated wormlike micelles.…”
Section: Idpa Primary Structurementioning
confidence: 99%
“…To investigate the role of single amino acid mutation, we designed IDPA we found that the hydrophilic domain (i.e., the disordered peptide) and its interactions controlled the complex aggregations at low pH and served to strengthen the interaction between worm-like micelles. 47 Here, we focus on the intermediate pH region where a single mutation can potentially fine-tune the phase transition point.…”
Section: S15)mentioning
confidence: 99%
See 2 more Smart Citations